Application of a gratuitous induction system in Kluyveromyces lactis for the expression of intracellular and secreted proteins during fed-batch culture - Wannana Panuwatsuk (2018)
A gratuitous induction system in the yeast Kluyveromyces lactis was evaluated for the expression of intracellular and extracellular products during fed-batch culture. The Escherichia coli lacZ gene (β-galactosidase; intracellular) and MFα1 leader-BPTI cassette (bovine pancreatic trypsin inhibitor; extracellular) were placed under the control of the inducible K. lactis LAC4 promotor, inserted into partial-pKD1 plasmids, and transformed into a ga1-209 K. lactis strain. To obtain a high level of production, culture conditions for growth and expression were initially evaluated in tube cultures. A selective medium containing 5 g/L glucose (as carbon source) and 0.5 g/L galactose (as inducer) demonstrated the maximum activity of both β-galactosidase and secreted BPTI. This level of expression had no significant effect on the growth of the recombinant cells; growth rate dropped by approximately 11 %, whereas final biomass concentrations remained the same. In shake-flask culture, biomass concentration, β-galactosidase activity, and BPTI secreted activity were 4 g/L, 7664 U/g dry cell, and 0.32 mg/L, respectively. Fed-batch culture (with a high glucose concentration and a low galactose [inducer] concentration feed) resulted in a 6.5-fold increase in biomass, a 23-fold increase in β-galactosidase activity, and a 3-fold increase in BPTI secreted activity. The results demonstrate the success of gratuitous induction during high-cell-density fed-batch culture of K. lactis. A very low concentration of galactose feed was sufficient for a high production level. © 2003 Wiley Periodicals, Inc.